DRUGS INTAKE GENERATES FREE SEX BEHAVIOUR TOWARD TEENAGER - Ai Kusmiati Asyiah; Ristina Siti Sundari; Dudu Risana (Jurnal Sosial Humaniora, 2021)
Drugs intake causing free sex behavior toward teenager at Tasikmalaya then this matter has been worrying us. Promiscuity as teenager opinion is the common activity, instead give the bad impact either for health, norm or social among families and environment. It influence to future for teenager themselves and then could get worse for next generation. The research aimed to know whether correlation between drugs intake and promiscuity deal with teenager in Tasikmalaya. The method used survey and case study then analyzed by Rank Spearman Correlation Test toward 26 respondents using a questionnaire. The research indicated that there is the significant correlation between drugs intake and promiscuity. The more dragging in drugs intake is more doing free sex due to promiscuity. The weighted value of drugs intake is 78,5% and also free sex is 67,2%. It is necessary to do spiritual or religion approach and positive activity such as art, sport, organization or gardening regard to personality development to raise belief, safety and health either physically and mentally.